Answer:
Explanation:
Equation of a parabola with vertex (h, k) is given by,
y - k = a(x - h)²
Equation of a function 'f' with vertex (0, 3) will be,
y - 3 = a(x - 0)²
y - 3 = ax²
Since, graph of this function passes through (1, 4),
4 - 3 = a(1)²
a = 1
Therefore, equation will be,
y - 3 = (x - 0)²
f(x) = x² + 3
Equation of function 'g' with vertex at (0, -3) will be,
y - (-3) = a(x - 0)²
y + 3 = ax²
y = ax² - 3
Since, the graph passes through (1, -1),
-1 = a(1)² - 3
a = 2
Therefore, equation will be,
y = 2x²- 3
g(x) = 2x² - 3
Equation of the function 'j' with the vertex (0, -3) will be,
y - (-3) = a(x - 0)²
y + 3 = ax²
y = ax²- 3
Since, the graph of the function passes through (1, -5),
-5 = a(1)² - 3
a = -2
Therefore, function 'j' will be,
j(x) = -2x² - 3
Equation of the function 'h' with the vertex (0, -3) will be,
y - (-3) = a(x - 0)²
y + 3 = ax²
y = ax² - 3
Since, the graph of the function passes through (2, 1)
1 + 3 = a(2)²
4 = 4a
a = 1
Therefore, equation of the function 'h' will be,
h(x) = x² - 3